Analisis Pemahaman Pengguna Fitur Cardless Withdrawal pada BSI Mobile Banking dalam Transaksi Tarik Tunai (Studi Kasus Mahasiswa Perbankan Syariah Angkatan 2021 UIN Bukittinggi) - Khairimatulhusna Khairimatulhusna; Ilham Ilahi (ARZUSIN, 2025)
This study is motivated by the low level of understanding among some students of the Sharia Banking program at UIN Bukittinggi regarding the cardless withdrawal feature on BSI Mobile Banking for cash withdrawal transactions. The primary objective is to identify the factors influencing students' understanding of this feature. A qualitative method was employed, with primary data collected through interviews and documentation. Data analysis followed the stages of data reduction, data display, and conclusion drawing. The findings reveal that 90% of informants understand the concept and functionality of the cardless withdrawal feature, indicating the effectiveness of BSI’s outreach efforts. Approximately 65% of informants have used the feature, while the rest have not, citing reasons such as habitual reliance on traditional methods, lack of necessity, or limited technical information. Based on the Diffusion of Innovations framework, the feature is perceived to have a relative advantage due to its convenience, time efficiency, and enhanced security compared to conventional withdrawal methods. It is also considered compatible with students’ digital transaction habits and aligns with the modernization of sharia banking services. The feature is rated as low in complexity, with initial technical barriers easily overcome. Its high trialability—allowing use without financial risk—and observability, through visible use at ATMs and app notifications, further influence adoption. The study concludes that factors such as perceived advantage, alignment with values and habits, and ease of use significantly contribute to enhancing students’ understanding and adoption of the cardless withdrawal feature in the context of sharia banking.